Rapid and automated quantification of TDP‐43 and FUS mislocalisation for screening of frontotemporal dementia and amyotrophic lateral sclerosis gene variants. (1st February 2022) - Oyston, Lisa J; Ubiparipovic, Stephanie; Fitzpatrick, Lauren; Hallupp, Marianne; Boccanfuso, Lauren M; Kwok, John B; Dobson‐Stone, Carol
Abstract: Background: Identified genetic mutations account for ∼50% of familial frontotemporal dementia (FTD) and ∼70% of familial amyotrophic lateral sclerosis (ALS) cases, however, for the remainder of patients the origin of the disease is uncertain. Post‐mortem, affected neurons from 97% of ALS and ∼50% of FTD patients show cytoplasmic mislocalisation of the typically nuclear proteins, TDP‐43 and/or FUS. We exploited this predominant neuropathological feature to develop a high‐throughput, automated method for the quantification of cytoplasmic TDP‐43 and FUS in human cell lines. Method: Utilising fluorescently tagged cDNA constructs to identify cells of interest, fluorescence intensity of TDP‐43 or FUS in the nucleus and cytoplasm of HEK293 and SH‐SY5Y cells was measured from confocal microscope images using the freely available analysis software, CellProfiler. The assay was validated using known ALS‐causative mutations in the genes encoding TDP‐43 ( TARDBP ) and FUS, and pharmacological interventions known to cause TDP‐43 and FUS mislocalisation. The ability of the assay to detect effects of a secondary gene on endogenous TDP‐43 was tested using CYLD wild‐type and mutant constructs. Results: Expression of known TARDBP and FUS mutations showed significantly higher cytoplasmic to nuclear ratios when compared to wild‐type protein. Treatment with apoptosis inducers MG132 and staurosporine induced a similar effect. Lastly, we recapitulated the effect of the CYLD FTD‐ALS mutation p.M719V on TDP‐43 mislocalisation, as observed previously by manual counting of primary mouse neurons [Dobson‐Stone et al 2020, Brain 143:783‐799]. Conclusion: The current study validates our methodology as a novel in vitro technique for the quantification of TDP‐43 or FUS mislocalisation that can be used to rapidly and systematically assess the pathogenicity of predicted FTD/ALS gene variants. This methodology can be employed to aid genetic diagnosis of patients carrying novel variants in known FTD/ALS genes, and in the prioritisation of novel candidate genes for further functional analysis.